Yo Frankie! the Apricot Open Game project (Blender Foundation, 2010)
"Yo Frankie!" is a 3D game about a pesky rodent who's biggest Joy is to tease the other animals, annoy the crap out of everyone and even ruthlessly destroy innocent forest life!